Physical investigation of thionine-graphene nanocomposite synthesized using different concentrations of graphene oxide / Muhammad Aidil Ibrahim ... [et al.] - Ibrahim, Muhammad Aidil; Tunku Kudin, Tunku Ishak; Hassan, Oskar Hasdinor; Ali, Ab Malik Marwan; Yahya, Muhd Zu Azhan (Universiti Teknologi MARA Cawangan Pahang, 2019)
Nanomaterials such as graphene is popular amongst researchers because of its capability to increase electrical conductivity. In some researches, graphene was composited with thionine to induce stability when dispersed in water-based solvents especially in fabricating electrodes for biosensor applications. In this research, the concentration of graphene in the ThionineGraphene (Th-G) nanocomposite was varied to observe the stability of the composition produced. Different concentrations of graphene oxide (GO), 0.1, 0.3, 0.6 and 0.9 mg/mL were mixed with 2 mM thionine producing different Th-G samples and were observed through Scanning Electron Microscopy (SEM). Ultraviolet-visible spectroscopy (UV-vis) characterization were used to investigate the π-π interaction of graphene with thionine and to confirm the presence of both molecules in the samples. Physical observation of Th-G nanocomposite with 0.1mg/mL of graphene physically appeared to be most stable. While the UV-vis investigation confirms the presence of π-π interaction hence further proves the stability of the nanocomposite containing 0.1 mg/mL of GO when the absorbant peaks of graphene and thionine were the most prominent compared to the other samples